Indonesian Diaspora, A Cultural Property Asset with the Potential in Participation for Advancement of the Nation - Khotimah , Novy Khusnul; Kushardiyanti, Dessy (ELITE JOURNAL, 2023)
ABSTRACT This study aims to explore the potential of the Indonesian Diaspora to increase cultural recognition, economic welfare and social aspects through agents of the Indonesian Diaspora spread all over the world. Most of the Indonesian diaspora are migrants consisting of various professions. Some of them settled and changed their nationality, some of them are descendants, but there are also those who still retain Indonesian citizenship and contribute greatly to this country as we are familiar with PMI (Indonesian Migrant Workers). A descriptive qualitative approach was used in this study with data collection techniques in the form of literature studies through reference relevant to problems, government policies and case studies related to the development of the Indonesian Diaspora. The theory used is Intercultural Communication by looking at the Diaspora phase in involving all cultural structures in communication actions as part of the adaptation process. In the end it can be concluded that the contribution made by the diaspora is also quite large as an example is PMI (Indonesian Migrant Workers). The value of remittances or money transfers for migrant workers from PMI reaches IDR 130 trillion per year for Indonesia. The amount which even exceeds the contribution of the tourism sector and taxes from the mining sector, shows that the Diaspora's contribution to this country is very large and in the cultural communication that is carried out, the Indonesian Diaspora has gone through all phases of adaptation so that it will be easier to deliver Indonesia's potential to the international world. through acts of communication carried out Keywords: Intercultural Communication, Diaspora, Assets, Culture